Evaluating the influence of phosphorus supply on photosynthetic and agronomic performance of two breeding lines of common bean grown under acidic soil and high temperature stress - Suárez, Juan Carlos; Anzola, Jose Alexander; Vanegas, Jose Ivan; Contreras, Amara Tatiana; Idupulapati, Rao M. (2025)
High temperature stress has a significant effect on the physiological response of the bean crop ( Phaseolus vulgaris L.) and the supply of phosphorus (P) can influence photosynthetic performance, mobilization of photoassimilates and alleviate heat stress. The objective of this study was to evaluate the influence of increasing P supply on the response of the photosynthetic apparatus of two breeding lines of common bean grown in acidic soil under high temperature stress conditions in a screenhouse. A completely randomized block design with factorial arrangement was used: i. five levels of P supply (P0, P15, P30 and P45 kg ha -1 ; and P supplied through organic matter [PSOM at P25]), and ii. two bean lines (BFS 10, SEF 10) with a total of ten treatments and four replications. During the study, the ambient temperature rose to 37°C and 29°C during the day and night, respectively, a high temperature stress condition that significantly affected the functioning of the photosynthetic apparatus of the two bean lines evaluated. Under these growing conditions, the bean lines adjusted in canopy temperature, reducing leaf temperature by 3.6 to 4.0°C compared to ambient temperature, a process performed more efficiently by SEF 10 compared to BFS 10. Increased P supply improved electron transport chain function, ATP production, PSII photochemical efficiency (F v /F m ), the fraction of energy devoted to the photosynthesis process (ΦII); and reduced the amount of energy in the form of heat (ΦNPQ) as the need for heat dissipation manifested through leaf temperature difference (LTD). These adjustments to photosynthetic apparatus translated into superior agronomic performance through greater partitioning of dry matter into grain yield (GY) as revealed by partitioning indices such as pod partitioning index (PPI), pod harvest index (PHI) and harvest index (HI), and yield components including pod number per area (PNA) and seed number per area (SNA). Increased P supply increased leaf P concentration and alleviated the effects of high temperature on the functioning of the photosynthetic apparatus in both common bean lines (BFS 10 and SEF 10); and accumulation of sugars in pods and seeds facilitated improved seed yield. These two bean lines can serve as parents in bean breeding programs that aim to combine low P tolerance with high temperature tolerance in acid soil regions of the tropics.